ANALISIS PENERAPAN AKUNTANSI PAJAK PENGHASILAN PASAL 23 PADA PERUSAHAAN JASA PERBANKAN - Lalu Takdir Jumaidy; D. Tiallurra Della Nabila; Anggun Hilendria (Jurnal Riset Akuntansi, 2020)
This study aims to determine the application of income tax accounting article 23 in the business activities of Mataram BTN Bank. The results of the study explained that Mataram BTN Bank has approved the payment of income tax article 23 on vehicle rental in accordance with applicable tax regulations and has recorded accounting for vehicle rental costs and taxes on vehicle rental, calculates tax on vehicle rental, tax payment and tax reporting.